2011
DOI: 10.1370/afm.1249
|View full text |Cite
|
Sign up to set email alerts
|

Understanding Patients' Experiences of Treatment Burden in Chronic Heart Failure Using Normalization Process Theory

Abstract: PURPOSE Our goal was to assess the burden associated with treatment among patients living with chronic heart failure and to determine whether Normalization Process Theory (NPT) is a useful framework to help describe the components of treatment burden in these patients. METHODSWe performed a secondary analysis of qualitative interview data, using framework analysis, informed by NPT, to determine the components of patient "work." Participants were 47 patients with chronic heart failure managed in primary care in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
399
2
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 298 publications
(420 citation statements)
references
References 38 publications
8
399
2
1
Order By: Relevance
“…The clinical relevance of treatment burden has been established for consequential outcomes such as adherence to prescribed treatments, quality of life, and health services utilization. 13,22,[36][37][38] That aspects of burden associated with managing health was more commonly experienced by persons in worse health underscores the practical importance of incorporating individual perspectives and preferences in prioritization of possible treatment and preventive regimens by balancing evidence of clinical benefit with minimizing burdens. [39][40][41] Current delivery and reimbursement structures fail to support providers' ability to comprehensively deliberate with patients about the risks and benefits of alternative treatment options and preventive strategies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The clinical relevance of treatment burden has been established for consequential outcomes such as adherence to prescribed treatments, quality of life, and health services utilization. 13,22,[36][37][38] That aspects of burden associated with managing health was more commonly experienced by persons in worse health underscores the practical importance of incorporating individual perspectives and preferences in prioritization of possible treatment and preventive regimens by balancing evidence of clinical benefit with minimizing burdens. [39][40][41] Current delivery and reimbursement structures fail to support providers' ability to comprehensively deliberate with patients about the risks and benefits of alternative treatment options and preventive strategies.…”
Section: Discussionmentioning
confidence: 99%
“…Questions to assess health care decision-making preferences and treatment burden were developed based on existing literature, and were devised for broad population relevance and feasible administration within a national survey. This emphasis varies from the prevailing evidence base that has focused on decision-making preferences and experiences of care with a specific health condition, 13,22,38 clinical situation, 36,37 or medical encounter, 14,28 although measures to ascertain these constructs are evolving. 2,49,50 Study findings are limited to older adults' perspectives, and do not encompass perspectives of family members and close friends who may share or assume responsibility for management of health care activities.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, patients describe professionally driven healthcare services that focus on delivering guideline‐based medical treatment. This is sometimes burdensome in itself, and there is often poor co‐ordination and a lack of continuity of care 16, 21, 22. Heart failure management programmes have been developed in several countries to address many of these issues.…”
Section: Prognosticationmentioning
confidence: 99%
“…Present communication paths, predominantly offline, and often by referral letter necessitating an outpatient review do not allow easy communication between professionals and can lead to disjointed care. For example, one study demonstrated that HF patients reported too many medications and appointments, barriers to accessing services, fragmented and poorly organized care, lack of continuity, and inadequate communication between health professionals as components to treatment burden that they experienced 10. Optimal and timely communication between GPs and cardiologists can help ensure that appropriate care is provided and reduce many of these elements of treatment burden.…”
Section: Discussionmentioning
confidence: 99%